Influence of weather and atmospheric pollution on physical activity in patients with COPD. Issue 1 (December 2015) - Alahmari, Ayedh; Mackay, Alex; Patel, Anant; Kowlessar, Beverly; Singh, Richa; Brill, Simon; Allinson, James; Wedzicha, Jadwiga; Donaldson, Gavin
Abstract Rationale Information concerning how climate and atmospheric pollutants affects physical activity in COPD patients is lacking and might be valuable in determining when physical activity should be encouraged. Methods Seventy-three stable COPD patients recorded on daily diary cards worsening of respiratory symptoms, peak expiratory flow rate, hours spent outside the home and the number of steps taken per day. Pedometry data was recorded on 16, 478 days, an average of 267 days per patient (range 29-658). Daily data for atmospheric PM10 and ozone (O3 ) were obtained for Bloomsbury Square, Central London from the Air Quality Information Archive databases. Daily weather data were obtained for London Heathrow from the British Atmospheric Data Archive. Results Colder weather below 22.5 °C, reduced daily step count by 43.3 steps day per°C (95 % CI 2.14 to 84.4;p = 0.039) and activity was lower on rainy than dry days (p = 0.002) and on overcast compared to sunny days (p < 0.001). Daily step count was 434 steps per day lower on Sunday than Saturday (p < 0.001) and 353 steps per day lower on Saturday than Friday (p < 0.001). After allowance for these effects, higher O3 levels decreased activity during the whole week (-8 steps/ug/m3;p = 0.005) and at weekends (-7.8 steps/ug/m3;p = 0.032). Whilst, during the week PM10 reduced activity (p = 0.018) but not during the weekend. Conclusions Inactivity of COPD patients is greatest on cold, wet and overcast days and at the weekends. This study also provides evidence of an independent effect of atmospheric pollution at high levels.